Comparing the Microbial Community in Four Stomach of Dairy Cattle, Yellow Cattle and Three Yak Herds in Qinghai-Tibetan Plateau - Jinwei Xin; Jinwei Xin; Zhixin Chai; Chengfu Zhang; Chengfu Zhang; Qiang Zhang; Qiang Zhang; Yong Zhu; Yong Zhu; Hanwen Cao; Hanwen Cao; Jincheng Zhong; et al. (Frontiers in Microbiology, 2019)
Yak (Bos grunniens) is an unique ruminant species in the Qinghai-Tibetan Plateau (QTP). The ruminant gastrointestinal tract (GIT) microbiota is not only associated with the nutrients metabolism, but also contributes to the host’s local adaptation. Examining the microbiota between cattle and yak in different geography could improve our understanding about the role of microbiota in metabolism and adaptation. To this end, we compared the microbiota in rumen, reticulum, omasum, and abomasum of dairy cattle, yellow cattle, and three yak herds (WQ yak, SZ yak, and ZB yak) lived in different altitude, based on sequencing the bacterial 16S rRNA gene on Illumina Miseq. The bacterial diversity was significantly different among five breeds, whereas the difference among four stomach regions is limited. The phyla Bacteroidetes and Firmicutes were the dominated bacteria regardless of breeds and regions. The nonmetric multidimensional scaling (NMDS) results showed that the microbiota in dairy cattle, yellow cattle and WQ yak significantly differed from that in SZ yak and ZB yak for all four stomach compartments. Canonical correlation analysis revealed that Prevotella and Succiniclasticum spp. were abundant in dairy cattle, yellow cattle and WQ yak, whereas the Christensenellaceae R7 group and the Lachnospiraceae UCG 008 group were prevalent in SZ yak and ZB yak. Moreover, the microbiota in WQ yak was significantly different from that in SZ yak and ZB yak, which were characterized by the higher relative abundance Romboutsia spp., Eubacterium coprostanoligenes, Acetobacter spp., Mycoplasma spp., and Rikenellaceae RC9 group. Overall, these results improves our knowledge about the GIT microbiota composition of QTP ruminant.